Development of the RISE Vibration Monitor: RVM - Edholm, Tobias; Högberg, Jesaja S. (My University, 2022)
Vibrations are responsible for the largest single part of workplace related injuries in Sweden. There is an ISO-standard which is used to estimate how harmful vibrations are and how long one can be exposed without risking damage, however it does not take into account ultra high frequency vibrations, those above 1250 Hz. Recent studies indicate that these vibrations might be more harmful than previously thought and that the current standard might not be sufficient to protect against all kinds of vibration-induced injuries. To remedy this problem the current ISO standard will be updated to better reflect the reality of what vibrations are harmful. However there is a lack of data to base the updated standard on. To gather the necessary data the client, Research Institutes of Sweden - RISE, has created a prototype instrument used to measure the ultra high frequency vibrations which contemporary instruments cannot measure accurately. The prototype includes electronics, a 3D-printed case, and a MATLAB interface. The aim of this project was to improve the usability and user experience of interacting with this instrument. The electronic components were to remain as they were, but the other parts could be changed freely. Additionally some accessories were to be explored, a carrying bag and a remote trigger for the instrument. The deliverables should be of such a fidelity that they can be sent to a contract manufacturer with little to no work from the client. The project was carried out in an iterative manner but began with investigations of the current state of the art of contemporary measurement instruments. This was followed by user research to understand the needs and wants of the users. Then followed concept ideation where different solutions to the needs and wants were investigated. The biggest part of the project was concept creation and refinement where solutions and ideas from the ideation were put together into a viable product which was then evaluated. The outcome of the project is a concept called The Rise Vibration Monitor - RVM consisting of a new front-end built in MATLAB which can be connected to the current MATLAB back-end as well as a manufacturing ready design concept for the instrument body and a carrying bag. Some design has also been done to create a remote trigger but at a lower fidelity which will require more work before it can be sent to manufacturing. These designs are meant to improve usability of the instrument which will hopefully in turn increase the quality of the measurements being created in the field. There is more work that can be done to improve the designs, especially on the hardware side. If the batch size were to be increased it would be worth looking at ways of miniaturizing the electronics which would allow for making the dimensions of the whole instrument smaller.
Keywords: User experience, vibrations, user research, UX/UI, work related injuries.